2011 IEEE International Workshop on Information Forensics and Security 2011
DOI: 10.1109/wifs.2011.6123131
|View full text |Cite
|
Sign up to set email alerts
|

ElectroMagnetic analysis (EMA) of software AES on Java mobile phones

Abstract: Abstract-Smartphones, whose market share has increased by 54% between 2009 and 2010, is one of the favored platform for "Convergence Computing". Convergence Computing is a technology in which a single device can provide various services without any restrictions from external devices or networks. Today, smartphones as convergent single device have diverse functions and features such as calling, Internet surfing, game playing, banking, storage of personal and professional data, etc. Some of these use encryption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…Starting with iOS 9, Com-monCrypto uses a new EC implementation, including sidechannel mitigation techniques such as operand-independent control flow and Montgomery-ladder multiplication. 5 Our current attacks are not applicable to this new EC implementation, and we have no evidence that it is vulnerable. CoreBitcoin.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Starting with iOS 9, Com-monCrypto uses a new EC implementation, including sidechannel mitigation techniques such as operand-independent control flow and Montgomery-ladder multiplication. 5 Our current attacks are not applicable to this new EC implementation, and we have no evidence that it is vulnerable. CoreBitcoin.…”
Section: Discussionmentioning
confidence: 85%
“…Key-Extraction Side-Channel Attacks on Phones. High bandwidth electromagnetic attacks (sampling at clockrate speeds) on symmetric ciphers were demonstrated by Aboulkassimi et al [5] on Java-based feature-phones. Attacks at clock-rate frequencies on public key cryptography were also recently demonstrated by Goller and Sigl [33] on Android smartphones running a naive square-and-sometimesmultiply RSA, with the phone's shielding plate often removed.…”
Section: Related Workmentioning
confidence: 99%
“…Attacks were performed in the last few years on advanced system. In [8], Aboulkassimi et al attacked a software implementation of AES under JAVA ME using EM measures. In [9], Longo et al added an OS and attacked a SoC running under Debian to extract AES encryption key exploiting electro-1 https://dx.doi.org/10.1145/3304080.3304084 Authors' version Proceedings of the Sixth Workshop on Cryptography and Security in Computing Systems CS2 2019 magnetic emanations.…”
Section: Previous Attacks On Socmentioning
confidence: 99%
“…Aboulkassimi et al [29] performed an EM attack on symmetric ciphers by capturing signals at the device clock rate on a Java based cellphone. However, they placed a MicroSD extension cable to the MicroSD card to extract EM information.…”
Section: Electromagnetic Attacksmentioning
confidence: 99%
“…In addition, the research in [34] recently demonstrated the ability to recover partial (12 out of the 16 subkeys) AES-128 cryptographic keys from a Raspberry Pi. As it is a new field the research [27][28][29][30][31][32][33][34] has followed attacks introduced by targeting smartcards, RFID tags, FPGAs and microcontrollers. However, each attack against these higher frequency devices had different approaches with regards to recovery EM information and applying digital filtering techniques to recover sensitive information.…”
Section: Electromagnetic Attacksmentioning
confidence: 99%